Implementation of Qur'anic Verses and Hadiths About Work Behavior, Responsibility and Motivation - Maryani yani (International Journal of Southeast Asia, 2021)
Islam as a religious teaching that has a vision of rahmatan lil'alamin contains teachings that are able to shape a person's personality who implements divine messages (Alquran) and prophetic messages (hadith) in daily behavior -day. The obligation to study, work, hold fast and convey the mandate, and accountability for deeds before Allah SWT is a small part of Islamic teachings that allow a Muslim to have good work behavior. Commitment, motivation and job satisfaction (either together or separately) will be higher when HR policies create workforce capabilities, reward motivation and provide opportunities for participation. Fourth, HR policies to develop capabilities, motivation and opportunities must exist and reinforce each other. HR policies and reward practices that are implemented and enforced by the leadership can trigger discretionary behavior which is characterized by a change in attitude. It can increase or weaken if the policy is not in accordance with the organizational culture and values adopted. The success of the work done will provide experience that can help in acting in the future.